Trajetórias, lutas e “sentidos” no jornalismo esportivo em São Luís - COELHO, José Hailton Costa (2023)
In this paper we analyze the constitution of sports journalism in São Luís (MA), as well as, the meanings and perceptions of this activity from the construction of profiles linked to this space. In the national context, the "literati" have undertaken narratives about sports, and produced a brand for the news conditions. The changes that have occurred in the production of sports journalism - with the incorporation of technologies, radio, television and internet -, have caused the emergence of new "profiles" of journalists in this space, which is the main focus of this research. Sports journalists from São Luís were studied, for characterization between "new" and "classic", with the aim of studying the metamorphosis that the sports journalistic space has undergone in the early twentieth century until the XXI century, with emphasis on the analysis of technologies in radio journalism. The agents studied were classified as belonging to the "new" and "old" generation of sports journalism. Based on this cut, profiles were produced, which analyzed, characterized changes in the broader space of journalism and sports journalism, as well as evidenced the legitimate grammars in this arena.